Parliamentary information in regional parliaments in Spain: evaluation of web presence and social media sites - Merino Medina, Daniel Esteban; Muñoz Cañavate, Antonio (Revista General de Información y Documentación, 2014)
Since the advent of the Internet and the World Wide Web, parliaments have found them to be an effective channel through which to reach citizens. This has been enhanced by the so-called Web 2.0 with its new social media that have facilitated more communication with the outside. This paper presents a study applied to Spain’s Autonomous Community (regional) parliaments with the implementation of two recommendations of the Inter-Parliamentary Union (IPU): Guidelines for Parliamentary Websites, and Guidelines for the Use of Social Communication Media by Parliaments. The study instrument was a questionnaire based on these recommendations, and by observation of all the corresponding Web pages.